Economic assessment of integrated cancer and cardiovascular registries: The Barbados experience. (December 2016) - Martelly, Tanya N.; Rose, Angela M.C.; Subramanian, Sujha; Edwards, Patrick; Tangka, Florence K.L.; Saraiya, Mona
Highlights: Cardiovascular disease and cancer cost data were collected for one year. Registries incurred high fixed costs related to management and administration. Sharing fixed costs between multiple registries can reduce costs. Abstract: Background: This report describes the resources required to support the integrated approach of the Barbados National Registry for Chronic Non-communicable Diseases (BNR) to non-communicable disease (NCD) case registration, and to identify differences in cost for collecting and maintaining information on cancer and cardiovascular disease (CVD) case registration. Methods: We used the modified Centers for Disease Control and Prevention's International Registry Costing Tool to collect data from the CVD and cancer registries. We used cancer and CVD cost data for the annual period April 2014 through March 2015 to estimate the total cost and cost per case. We used prospectively collected average annual CVD cases, and for cancer cases we assumed 2 or 3 years are needed for retrospective data collection. Results: The Ministry of Health provided 56% of the resources for the registries. Labor accounted for over 70% of both registries' budgets, while management and administration, along with data collection and analysis, incurred the highest costs per case. Total variable cost activities related to data collection and analysis were higher for the CVD component (US$131, 297) than the cancer component (US$58, 917). The CVD cost per case (US$489) was in between the cancer 2-year (US$382) and the cancer 3-year (US$573) cost-per-case estimates. Conclusion: These findings indicate that there are substantial fixed costs related to management and administration of NCD registries. All registries need management and administration support. When registries are combined, management and administration costs can be shared. We project that registries that can share fixed-cost infrastructure are likely to incur a lower total cost per case.